PERLINDUNGAN HUKUM HAK PATEN ALAT STERILISASI UNTUK PENGOLAHAN TANDAN-TANDAN KELAPA SAWIT - Maulana Rizki Nov; Simona Bustani (Fakultas Hukum Universitas Trisakti, 2023)
The patent holder is the party who gets the exclusive right and the person who gets the exclusive right from the inventor. In the case between FWT and PT. SKL and PT. PKBR in the FWT case owned a patent for a palm oil sterilization tool, but PT.SKL and PT.PKBR used the patent without permission, in Court Decision 46/Pdt.Sus-Paten/2020/PNNiagaJkt.Pst. the judge rejected the exception of PT. SKL and PT. PKBR and in the main case rejected FWT's lawsuit against the lawsuit filed. Formulation of the problem: how is the legal protection for the patent holder of the invention? This article is a normative legal research, descriptive, using secondary data, qualitative data analysis, deductive conclusion. The results of the research, discussion and conclusion are that the judge's decision is not in accordance with the time of the incident, that the judge's decision declaring the plaintiff's convention lawsuit rejected does not provide a sense of legal protection for the plaintiff. So that the legal protection of patents for sterilizers for processing oil palm bunches and similar fruits in court decisions does not reflect the mandate of Law 13/2016.